2021
DOI: 10.1155/2021/1628959
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for the Diagnosis of Autism Spectrum Disorder Structured in Machine Learning and Verbal Decision Analysis

Abstract: Autism Spectrum Disorder is a mental disorder that afflicts millions of people worldwide. It is estimated that one in 160 children has traces of autism, with five times the higher prevalence in boys. The protocols for detecting symptoms are diverse. However, the following are among the most used: the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5), of the American Psychiatric Association; the Revised Autistic Diagnostic Observation Schedule (ADOS-R); the Autistic Diagnostic Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Wall et al [30] applied machine learning algorithms with data collected from multiple databases of information on ASD, including the Autism Genetic Resource Exchange (AGRE) and the Autism Consortium (AC). The authors indicated that artificial intelligence tools make it possible to differentiate between autism spectrum disorders and similar diseases with 100% accuracy [31].…”
Section: Ai and Its Tools In Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…Wall et al [30] applied machine learning algorithms with data collected from multiple databases of information on ASD, including the Autism Genetic Resource Exchange (AGRE) and the Autism Consortium (AC). The authors indicated that artificial intelligence tools make it possible to differentiate between autism spectrum disorders and similar diseases with 100% accuracy [31].…”
Section: Ai and Its Tools In Psychiatrymentioning
confidence: 99%
“…[30] zastosowali algorytmy uczenia maszynowego z danymi zgromadzonymi w wielu bazach informacji na temat ASD, w tym Autism Genetic Resource Exchange (AGRE) i Autism Consortium (AC). Autorzy wskazali, że narzędzia sztucznej inteligencji umożliwiają różnicowanie zaburzeń spektrum autyzmu oraz podobnych chorób ze 100% dokładnością [31].…”
Section: Ai I Jej Narzędzia W Psychiatriiunclassified
“…Logistic Regression is one of the most popular Machine Learning algorithms for binary classification, given a set of independent variables, and is used to predict a binary result (1 or 0, Yes or No, True or False) [32]. It has been applied successfully in various areas, such as Medicine [37], Finance [38], and Economics [39]. In this model, the probabilities describing the possible outcomes of a single trial are modeled using a logistic function, namely the logical relationship between a dichotomous response variable and a series of numerical (continuous, discrete) or categorical explanatory variables.…”
Section: Fundamentals Of the "Logistic Regression" Algorithmmentioning
confidence: 99%
“…In this model, the probabilities describing the possible outcomes of a single trial are modeled using a logistic function, namely the logical relationship between a dichotomous response variable and a series of numerical (continuous, discrete) or categorical explanatory variables. [37][38][39][40].…”
Section: Fundamentals Of the "Logistic Regression" Algorithmmentioning
confidence: 99%
“…The choice for ML was due to its great potential in generating knowledge from large databases (Andrade et al 2021b ). In turn, about the MCDA methodology, the study was based on Verbal Decision Analysis methods, such as Ordinal Classification (ORCLASS) and ZAPROS-IIIi (Andrade et al 2021a ). The use of VDA is related to the need for decisions that involve subjective knowledge used in qualitative choices.…”
Section: Introductionmentioning
confidence: 99%